Jagged edge - Barry, John 1933-2011 (Powerhouse Films, 2023)
"In einem Mordprozeß stehen sich ein ehrgeiziger Staatsanwalt, eine engagierte Rechtsanwältin und ein des Mordes an seiner Frau angeklagter Mann gegenüber. Ein Thriller, der durchgehend spannend die Hintergründe eines Mordfalles schildert; durch ansprechende Schauspielerleistungen, Kameraarbeit und Montage über dem Durchschnitt des Genres." [filmdienst.de]
Original: USA 1985
Indicator Blu-ray edition special features: High Definition remaster ; original stereo audio ; optional 5.1 surround audio ; The Guardian interview with Jeff Bridges (1990, 58 mins): archival audio recording of the legendary actor in conversation with critic Geoff Andrew at the National Film Theatre, London ; Killer business (2021, 23 mins): acclaimed screenwriter Joe Eszterhas revisits one of his favourite scripts ; Cutting edge (2021, 17 mins): editor Sean Barton recalls his time working on the film ; Music of loneliness (2021, 10 mins): analysis of John Barry’s score by author and musicologist David Huckvale ; original theatrical trailer ; radio spot ; image gallery: promotional and publicity material ; new and improved English subtitles for the deaf and hard-of-hearing
Bildformat 1.85:1
Keywords: Film; Blu-Ray-Disc